2018
DOI: 10.3389/fphar.2018.00481
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Exerts Cytotoxic Activity Against Multidrug-Resistant Tumor Cells via Targeting Autocrine Motility Factor Receptor (AMFR)

Abstract: Betulinic acid (BetA) is a naturally occurring pentacyclic triterpene isolated from the outer bark of white-barked birch trees and many other medicinal plants. Here, we studied betulinic acid's cytotoxic activity against drug-resistant tumor cell lines. P-glycoprotein (MDR1/ABCB1) and BCRP (ABCG2) are known ATP-binding cassette (ABC) drug transporters that mediating MDR. ABCB5 is a close relative to ABCB1, which also mediates MDR. Constitutive activation of the EGF receptor is tightly linked to the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…In addition, a study reported that betulinic acid decreases the growth of estrogen receptor (ER)-negative MDA-MB-231 breast cancer cells in vitro and in vivo by interactions with the microRNA-27a-ZBTB10-Sp-axis, causing increased cell death [48]. Furthermore, betulinic acid has been reported to exert cytotoxic activity against multidrug-resistant tumor cells by targeting autocrine motility factor receptor (AMFR), which is a ubiquitin E3-ligase cell surface glycoprotein that is known to play a role in metastasis, tumor progression, and recurrence [49]. Interestingly, a synergistic effect was observed in the anticancer activity when betulinic acid was used in combination with tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) or ionizing radiation [50,51].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a study reported that betulinic acid decreases the growth of estrogen receptor (ER)-negative MDA-MB-231 breast cancer cells in vitro and in vivo by interactions with the microRNA-27a-ZBTB10-Sp-axis, causing increased cell death [48]. Furthermore, betulinic acid has been reported to exert cytotoxic activity against multidrug-resistant tumor cells by targeting autocrine motility factor receptor (AMFR), which is a ubiquitin E3-ligase cell surface glycoprotein that is known to play a role in metastasis, tumor progression, and recurrence [49]. Interestingly, a synergistic effect was observed in the anticancer activity when betulinic acid was used in combination with tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) or ionizing radiation [50,51].…”
Section: Resultsmentioning
confidence: 99%
“…recorded upon treatments with DCB, compounds 1 , 3, and 4 were lower than with doxorubicin (Table 1). Previous studies also reported the hypersensitivity of CEM/ADR5000 leukemia cells to compound 1 as compared to its sensitive congener CCRF-CEM cells [34]. These data are indications that Dichrostachys cinerea and its constituents have the potential to combat cancer multidrug resistance.…”
Section: Discussionmentioning
confidence: 63%
“…However, preliminary antiproliferative effects of this plant were reported towards DU145 and 22Rv1 prostate cancer cells and HeLa cervical cancer cells, with the lowest IC 50 values of 8.04 μ g/ml recorded in 22Rv1 cells [7]. Also, betulinic acid is a well-known cytotoxic compound [34]. Its effects have been reported towards several cancer cell lines including sensitive and resistant phenotypes such as CCRF-CEM cells and CEM/ADR5000 leukemia cells, MDA-MB-231-pcDNA and MDA-MB-231/ BCRP breast adenocarcinoma cells, HEK293 and HEK293/ ABCB5 embryonic kidney cells, and U87.MG and U87.MG ΔEGFR glioblastoma cells with IC 50 values ranging from 15.1 μ M (against HEK293 cells) to 29.4 μ M (towards CCRF-CEM cells) [34, 36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis usually takes three or more stages with a maximum betulinic acid yield of 55% [1]. BA has a wide range of anti-tumor effects and exhibits anti-HIV activity [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%